2014
DOI: 10.4172/2161-1068.1000168
|View full text |Cite
|
Sign up to set email alerts
|

Pigments and Pathogenesis

Abstract: In recent years pigments have been identified in human nutrition to have a positive effect on human health and reduction to oxidative stress exposure. In the media it has become common wisdom that colourful food is naturally better to consume for humans and animals. Now recently it has been shown that pigments aid microbial species as well, and conversely these microbial pigments may result in more morbidity and mortality for the human host infected by these colourful microbes. Similar pigments that are availa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 32 publications
0
5
0
Order By: Relevance
“…Diverse pigmentation among the isolates were observed ranging from white to violet to brown may suggest differences in the virulence of the isolates in this study towards P. nigrum L. Duarte and Archer, (2003) suggested that different pigmentation of the pathogen may have different toxigenic activity. Similarly, Saviola (2014) also reported pigment production in pathogen associated with increment in their virulence towards the host. Shahnazi et al, (2012) reported that F. solani isolated from P. nigrum L. with dark red pigmentation showed stronger pathogenicity.…”
Section: Discussionmentioning
confidence: 84%
“…Diverse pigmentation among the isolates were observed ranging from white to violet to brown may suggest differences in the virulence of the isolates in this study towards P. nigrum L. Duarte and Archer, (2003) suggested that different pigmentation of the pathogen may have different toxigenic activity. Similarly, Saviola (2014) also reported pigment production in pathogen associated with increment in their virulence towards the host. Shahnazi et al, (2012) reported that F. solani isolated from P. nigrum L. with dark red pigmentation showed stronger pathogenicity.…”
Section: Discussionmentioning
confidence: 84%
“…A study found that pink pigment production in Acinetobacter wofii was induced by methanol as sole source of carbon [144]. Mycobacterium tuberculosis was found to produce carotenoid pigments in acidic stress at pH 5.0–6.0 and long-term growth in anaerobic culture conditions [145], and several other Mycobacterium species appeared to produce different pigments [146].…”
Section: Factors Affecting Pigment Productionmentioning
confidence: 99%
“…On the other hand, they may exhibit virulence in bacteria. Pathogens survive for long term in abscesses, immune cells, and invasiveness due to pigment production [27,28].…”
Section: Discussionmentioning
confidence: 99%